(untitled) (American Journal of Islam and Society, 2006)
Imagine that a struggling revolutionary movement is promising paradise after your defenseless country is unwillingly sucked into the maelstrom of total war; that the revolutionary leaders are highly respected men and women, many of whom were educated in the former colonial master’s homeland; and that the ruler, who is credited with single-handedly achieving your nation’s independence and enjoys near-divine status among the masses, joins the revolutionaries after being overthrown and calls upon you to do likewise. And then, full of post-victory idealism, imagine that you live for three years, eight months, and twenty days in the horror that introduced a new word into the English language: auto-genocide. Welcome to Democratic Kampuchea, whose ruling elite, the Khmer Rouge, targeted the author’s people, the Cham Muslims, for extermination: “The enemies of Angkar [the “Organization”] come in many categories, but the biggest enemies are the Cham. The plan is to destroy them all before 1980” (p. 6). This book is divided into five parts: “Introduction,” “S-21 Prisoner Cases,” “Analysis,” “References,” and “Appendix.” The “Introduction” deals with the controversial questions of how many Cham died under the Khmer Rouge (from 77,000 to 400,000-500,000) and how many lived in Cambodia before the Khmer Rouge took over (from about 250,000 to 700,000, the latter number being accepted by the Cham). Osman then moves on to how the Khmer Rouge sought to destroy community solidarity: turning Cham against Cham and children against parents, forbidding Islamic and Cham customs in toto, destroying the Qur’an and the keitab (a book explaining the Qur’an), making local leaders “disappear,” splitting up families during forced evacuations, and resettling the Cham among ethnic Khmer and Chinese. He also explains why he chose the thirteen case studies that make up the next part: “…there is sufficient documentation for study and research” (p. 8) ...